1995
DOI: 10.1159/000211330
|View full text |Cite
|
Sign up to set email alerts
|

Use of Human Skin Recombinants as an in vitro Model for Testing the Irritation Potential of Cutaneous Irritants

Abstract: Two human skin recombinants, the epidermis reconstructed on the deepidermized dermis (RE-DED) or on fibroblast-populated collagen matrix (Living Skin Equivalent, LSETM), were used to study the irritating effect of sodium lauryl sulfate (SLS). The extent of cytotoxicity induced after a 24-hour exposure period to increasing concentrations of SLS (0-5%) was evaluated on the basis of (1) morphological perturbations, (2) changes in the expression of differentiation-specific protein markers (keratin 1, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…However, for application of skin models in large-scale studies, quality control is of crucial importance. Since these models have mainly been used for relatively small-scale and in-house toxicity studies by research laboratories [8][9][10][11], their suitability for standardized screening and prediction of skin irritation and penetration in humans has not yet been fully accepted by regulatory authorities.…”
Section: Introductionmentioning
confidence: 99%
“…However, for application of skin models in large-scale studies, quality control is of crucial importance. Since these models have mainly been used for relatively small-scale and in-house toxicity studies by research laboratories [8][9][10][11], their suitability for standardized screening and prediction of skin irritation and penetration in humans has not yet been fully accepted by regulatory authorities.…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines are considered as a critical signal in the cascade of events leading to skin irritation and inflammation (Barker, et al, 1991;Ponec and Kempenaar, 1995). Among the number of cytokines, IL-l a is a major interleukin present in keratinocytes (Kupper, et al, 1986) and is associated with skin irritation (Corsini, et al, 1996a).…”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms have been associated with ICD and these are largely dependent on the nature of the irritant. Experimental and animal models have demonstrated that solvents such as acetone extract lipids from the stratum corneum [13], and anionic surfactants like sodium lauryl sulphate (SLS), cocbetaine and sodium dodecan sulphonate (SDS) damage keratin, involucrin, profilaggrin, and other protein structures responsible for preventing oversaturation of the stratum corneum and disorganization of the lipid bilayers [14][15][16].…”
Section: Pathophysiology Of Irritant Contact Dermatitismentioning
confidence: 99%